A Protocol for Rapid Multiplication of Gerbera jamesonii L. –A popular Cut Flower through Organogenesis - Islam, M. M; Mamun, A. A; Dash, P. K; Islam, M. R; Khanam,; S (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
A protocol for rapid multiplication of regenerated plants from callus, initiated from mature seeds of gerbera has been developed. Effect of gerbera genotypes and levels of IBA was investigated for callus formation and subsequent morphogenesis. Frequencies of callus were variable both with genotypes and IBA concentrations. ‘Pale yellow’ genotype and IBA 2 mgL-1 were identified most promising for callus differentiation. Multiple shoot regeneration was achieved on MS medium fortified with BAP 2.0 mgL-1 + IAA 1.0 mg L- 1. In vitro grown shoots were rooted on MS medium supplemented with IBA- 0.5 mgL-1. Maximum shoot regeneration (96%), shoot number callus-1 (9.86) and rooting (100%) was noticed for ‘pale yellow’ gerbera while ‘white’ genotype showed minimum plant regeneration (76%) and rooting (75%). Rooted plants were hardened before transplanting to soil. Survival rate of regenerated plants ranged from 57% to 89%. Maximum survival rate was found for the genotype ‘pale yellow’ and lowest was recorded in ‘white’ gerbera genotype